Percepção de perda de velocidade e caráter de esforço no agachamento em adultos jovens - Matos, Cleber Barbosa (2024)
INTRODUCTION: The velocity loss perception (VLP) has been investigated as a method to monitor neuromuscular fatigue without the use of velocity transducers. However, its effectiveness in individuals with different physical activity levels (PAL) and between genders remains underexplored. OBJECTIVE: To evaluate the VLP during the squat exercise in young adults. METHODS: A total of 53 volunteers were allocated according to their PAL (irregularly active n = 12, active n = 20, and highly active n = 21). A repeated measures two-way ANOVA was used for VLP at 10% (VLP10) and 30% (VLP30), repetitions performed at VLP (Rep VLP10 and Rep VLP30), maximal repetitions (Rep Max), and VLP between genders. Bonferroni post hoc tests were used for significant effects. Intraclass Correlation Coefficients (ICC 3, k) were calculated for VLP10 and VLP30. Absolute Error (AE) in VLP between groups and genders was assessed. Pearson correlations for VLP10 and Spearman correlations for VLP30 were used to identify potential relationships with %Rep. The Jamovi software was used, with the significance level set at p < 0.05. RESULTS: No statistically significant differences were found for all individuals or between different PAL groups in VLP10, VLP30, Rep VLP10, Rep VLP30, and Rep Max. Reliability was moderate for the highly active group in VLP30 (ICC = 0.64; 95% CI 0.24 – 0.83). Men showed a significant improvement in VLP30 (p = 0.015) compared to women. There was a weak correlation with %Rep in the retest of VLP10 and VLP30. CONCLUSION: The VLP approach tends to be an unreliable and imprecise method for individuals with different PAL, with initial bias. VLP varies between genders, with men showing improvement in VLP30 on retest. There is a tendency among individuals to overestimate in VLP10 and underestimate in VLP30. Additionally, VLP show a weak correlation with %Rep, indicating it as imprecise method for monitoring fatigue.